Access to Knowledge in Africa The role of copyright - Armstrong, Chris; De Beer, Jeremy (UCT Press, 2010)
The emergence of the Internet and the digital world has changed the way people access, produce and share information and knowledge. Yet people in Africa face challenges in accessing scholarly publications, journals and learning materials in general. At the heart of these challenges, and solutions to them, is copyright, the branch of intellectual property rights that covers written and related works. This book offers an understanding of the legal and practical issues posed by copyright for access to learning materials in Africa, and identifies the relevant lessons, best policies and best practices that would broaden and deepen this access. This book is based on the work of the African Copyright and Access to Knowledge (ACA2K) research network, launched in late 2007 as a network of researchers committed to probing the relationship between copyright and learning materials access in eight African countries: Egypt, Ghana, Kenya, Morocco, Mozambique, Senegal, South Africa and Uganda.